2013
DOI: 10.1007/s12098-013-1066-z
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Iron Pot Cooking on Iron Status

Abstract: This pilot study demonstrated that iron rich recipes cooked in iron pot have a beneficial effect on iron status of children. Therefore, such food based strategies have the potential to alleviate iron deficiency anemia not only in children but also in other vulnerable sections of society like in pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…A final limitation of studies included in this review was limited reporting on iron content and bioavailability of food prepared with iron-containing cookware, ideal cooking conditions, adverse effects and cost-effectiveness. It is possible that most investigators chose to forgo measurement of iron content and bioavailability, because the effect of iron-containing cookware on these parameters has already been relatively well established [14, 18, 29, 4648]. However, other studies have shown that the iron content and availability of food prepared with iron cookware depends on cooking conditions, including the type of food prepared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A final limitation of studies included in this review was limited reporting on iron content and bioavailability of food prepared with iron-containing cookware, ideal cooking conditions, adverse effects and cost-effectiveness. It is possible that most investigators chose to forgo measurement of iron content and bioavailability, because the effect of iron-containing cookware on these parameters has already been relatively well established [14, 18, 29, 4648]. However, other studies have shown that the iron content and availability of food prepared with iron cookware depends on cooking conditions, including the type of food prepared.…”
Section: Discussionmentioning
confidence: 99%
“…Drs. Anuradha Khadilkar and Veena Ekbote were contacted for more information and potentially missing data regarding a study published by Kulkarni et al [29].…”
Section: Methodsmentioning
confidence: 99%
“…By 400 BCE iron largely replaced bronze and ceramic as the principle material for cooking vessels (Wells, 1984). Cooking in iron pots results in some iron uptake in the food, particularly when cooking dairy products (Kröger‐Ohlsen et al, 2002; Geerligs et al, 2003; Charles et al, 2011; Adeniyi and Ajayi, 2013; Kulkarni et al, 2013). As milk begins to sour, lactic acid bacteria can accidently or purposefully be added to the mixture to begin the fermentation process (Kunji et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…One explanation is that non-heme iron is found in abundance in plant sources such as legumes, roots and tubers and their bio-availability is increased with concomitant intake of vitamin C-rich diet [10,38,39,41]. Other explanations for increased bio-availability of non-heme iron include baking chappathis in iron plates and the addition of ascorbic acid to cereals and pulses [42,43]. However a study on young women from Bangalore (India) estimates that only 2.8% of iron (non-heme) is available from plant sources [44].…”
Section: Discussionmentioning
confidence: 99%